Development of an e-practical guidebook based on chemo-entrepreneurship integrated with islamic values - Hanik Nurul Inayah; Mohammad Agus Prayitno; Mufidah, Mufidah (Yayasan Insan Mulia Bima, 2024)
Development of an E-Practical Guidebook Based on Chemo-Entrepreneurship Integrated with Islamic Values. The aim of this research is to determine the characteristics, feasibility and response of students to the E-Practical Guidebook based on chemo-entrepreneurship integrated with Islamic values ​​in acid-base material. This research uses a 4D instructional development model which is limited to the development stage. The test subjects included students in class XI MIPA 5 at SMAN 12 Semarang. Data collection instruments used interviews, literature studies, and questionnaires. Characteristics of the development product in the form of an E-Practical Guidebook based on chemo-entrepreneurship which is linked to real life, equipped with economic analysis, integration of Islamic values ​​​​in each practice, there is an inspiring story of Muslim entrepreneurs, and a study of halal products in the closing section, accessed via the heyzine web platform. The results of validation tests by material experts and media experts show that the E-Practical Guidebook is declared very feasible, proven by the validation results by material and media expert validators, the ???? ̅ values ​​are 55.34 and 30.67 respectively. The results of student responses at the limited trial stage stated that the E-Practical Guidebook was included in the good category with an ???? ̅ value of 61.93 and an ideal percentage of 82.57%.